1995
DOI: 10.1001/archpsyc.1995.03950150062011
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Social Phobia

Abstract: Generalized social phobia (1) can be distinguished reliably from nongeneralized social phobia, (2) is a valid subtype, and (3) may characterize a familial form of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…According to Turk et al, females tend to have a higher risk for social anxiety disorder [35]. Social anxiety disorder is reported to be more likely to develop in younger people [36,37]. However, in this study the mean age of subjects in the high LSAS group was higher than that in the low LSAS.…”
Section: Discussioncontrasting
confidence: 63%
“…According to Turk et al, females tend to have a higher risk for social anxiety disorder [35]. Social anxiety disorder is reported to be more likely to develop in younger people [36,37]. However, in this study the mean age of subjects in the high LSAS group was higher than that in the low LSAS.…”
Section: Discussioncontrasting
confidence: 63%
“…Past research suggests that performance-related fears have a higher age of onset than more generalized interactional and observational social fears. [15, 24] Indeed, in the present sample, rates of endorsement for some of the performance subtype symptoms were significantly higher among youth ages 12 and above than youth ages 6–11. For example, 62.5% of SAD youth ages 12 and older endorsed “inviting a friend to get together” as a scenario that causes them significant anxiety compared with only 31.8% of SAD youth ages 6–11 [ X 2 (1) = 16.05, P = 000].…”
Section: Discussionmentioning
confidence: 49%
“…These findings have been noted among both adolescents and adults (Page, 1990;Santesso, Schmidt, & Fox, 2004). Individuals with SAD often suffer from co-occurring alcohol problems (Mannuzza et al, 1995), and self-report measures indicate that they use substances as a coping mechanism to combat feelings of anxiety and fear in social contexts (Smail, Stockwell, Canter, & Hodgson, 1984). Hartman (1986) found that shy individuals reported using illicit drugs and alcohol to decrease social anxiety compared to non-shy individuals.…”
Section: Psychological Disordersmentioning
confidence: 84%